(untitled) (Nordic Journal of African Studies, 1999)
This essay answers two broad questions. Firstly, what is Kalabari explanatory system, conceptual framework about? Secondly, what is the relationship between Kalabari conceptual scheme and the ‘structure and strategy’ of the Kalabari traditional firm (wari or canoe-house corporation)? The canoe house was, “a compact and well organized trading and fighting corporation, capable of manning and maintaining a war canoe.” This paper, using Horton’s framework of analysis supplemented with original insights, examines not only the various ways Kalabari world view affects the structure and strategy of the wari, but also how world view interacts with managerial decision-making process in the canoe-house corporation. The analysis shows that Kalabari administrative thinking features an “aggressive welfare consciousness” and a “timid subterranean market paradigm.” Second, the key to understanding the relationship between Kalabari world view and structure and strategy of the wari is to view the structure of the traditional firm as a form of classification with the capacity to control how its members interact. The Kalabari corporate structure followed three categories of gods (ancestors or duein, founding heroes or oru, and water-spirits or owuamaba’pu) and they both (corporate structure and the scheme of three forces) fitted into a basic ‘typology of three’ in Kalabari culture. The structure of the canoe-house corporation was linked up in same analogical and metaphorical basis with the conceptual framework. Structure begets strategy. Defining strategy against a competitor boils down to placing him at a position in the structure and assessing his social ties and then designing means to contain his threat.